Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Douglas C. Harr, December 19, 1987 - Harr, Douglas C.et al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Spirit Lake contributed by Douglas C. Harr, December 19, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed